2024
DOI: 10.29303/jp.v14i1.784
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK POLA SEBARAN DAN MORFOMETRIK Enhalus acoroides DI PULAU BADAK BADAK KOTA BONTANG KALIMANTAN TIMUR

Restu Putri Ananda,
Lily Inderia Sari,
Aditya Irawan

Abstract: Lamun berkontribusi terhadap produktivitas perairan pesisir dan berperan ekologis sebagai makro dan mikro habitat organisme. Tujuan penelitian adalah mengetahui karakteristik pola sebaran dan morfometrik E. acoroides di Pulau Badak Badak Kota Bontang. Penelitian ini dilaksanakan bulan Agustus 2023 – Januari 2024. Tegakan E. acoroides dihitung berdasarkan sebaran sub stasiun dengan menggunakan bingkai kuadrat 50x50cm dan untuk sampel morfometrik diambil 5 tegakan E. acoroides dimasing-masing bingkai kuadrat. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Determination correlation between density A. antiquanta and density seagrass nor correlation between height and width shell, height and total weight of the shell as well as width and total weight of the shell were used for analysis correlation Pearson's Product Moment (Fakhri et al 2016;Ananda et al, 2024).…”
Section: Correlation Density Anadara Antiquata To Density Seagrass An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Determination correlation between density A. antiquanta and density seagrass nor correlation between height and width shell, height and total weight of the shell as well as width and total weight of the shell were used for analysis correlation Pearson's Product Moment (Fakhri et al 2016;Ananda et al, 2024).…”
Section: Correlation Density Anadara Antiquata To Density Seagrass An...mentioning
confidence: 99%
“…. Seagrass beds in Badak Badak Island waters tend to be mono-specific composed of E. acoroides (Ananda et al, 2024;Setiawan et al, 2024). Zulhariadi et al, (2017) reported that seagrass beds dominated by Enhalus acoroides with a muddy substrate type tend to have an abundance of Anadara sp.…”
Section: Introductionmentioning
confidence: 99%